Cement-based solidification of ferro-alloy solid wastes - Cohen, Brett (Department of Chemical Engineering, 2024)
A literature review presents a background to cement-based S/S, cement hydration behaviour and mechanisms by which metals could be contained in S/S products, based on proposals by other workers. Cr and Zn were of particular interest in this work due to high levels being found in the wastes and the different mechanisms by which they have been found to interact with cement. Preliminary experiments identified conditions which were conducive to the effective setting of the monolith. Three operational variables were chosen as having significance in determining the quality of the resultant S/S product, namely water to solids ratio, cement content and curing time. Effective setting of the cement-waste product was found to require a preliminary wash of the untreated dust to remove much of this soluble chromium and other salts. It was identified furthermore that the solids required higher amounts of water for mixing than would be required for hardened cement pastes and concretes.